Efektivitas Cylindrical Grip terhadap Kekuatan Otot Ekstremitas Atas pada Pasien Stroke - Tri Wahyuni Ismoyowati; Fransisca Winandari; Desty Irlani; Dewi Setia Rini; Yenny Dwiutami (FORIKES, 2021)
Stroke is a blockage of blood flow that results in reduced or no blood flow to the brain. Blockage of the middle cerebral artery causes muscle weakness and contralateral spasticity, as well as sensory deficits (hemianesthesia) due to damage to the precentral and postcentral lateral gyrus. Muscle weakness in stroke patients will affect muscle contraction, reduced muscle contraction is caused by reduced blood supply to the hindbrain and midbrain, so that it can inhibit the main pathways between the brain and spinal cord. This study is a literature review from several databases Pubmed, Google Scholar, NIH, NCBI, Research Gate, Microsoft Academia, Sience Direct and Proquest which aims to determine the effectiveness of Cylindrical Grip on upper extremity muscle strength in stroke patients.The search for articles is limited from 2011 to 2021. The author uses the keywords